Ley que prioriza la esterilización de perros y gatos como componente de la política nacional de salud pública (Ley N.° 31311): Alcances y aplicabilidad en municipalidades de Lima Metropolitana - Talavera V., Mariana (2023)
The aim of this study was to determine the opinion of municipal officials about the scope and applicability of the law that prioritizes the sterilization of dogs and cats as a component of the national public health policy (Law N° 31311) in the municipalities of Metropolitan Lima. A descriptive observational study was designed based on interviews involving 27 of the 50 district municipalities of Metropolitan Lima (Lima Province and Callao Constitutional Province). Results showed that 63% mentioned that they were fully aware of Law N° 31311 and 44.4% knew that it was not yet regulated (until December 2022), 66.7% mentioned that they have not discussed implementing the law in their municipalities and 74.1% mentioned that they did not have funding for its implementation. Besides, 88.9% indicated that they did not have a municipal shelter and 74.1% considered that the implementation of a shelter in a municipal management would be complicated. All the respondents considered that it is important to sensitize the population about the benefits of sterilizing companion animals and 55.6% responded that the municipality has not carried out a situational diagnosis study of the animals. It is concluded that the little knowledge of Law N°. 31311 by the authorities and the lack of economic resources allocated for its implementation would have a negative effect on the applicability of said norm in the district municipalities of Metropolitan Lima.